Examining gender disparity of male undergraduates in textile technology and design at university level : the case of two universities in Zimbabwe - Mhlanga, Elphina; Mushoriwa, Taruvinga; Mavuso, Percival M. (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper examined why gender disparity of male undergraduates taking Textile Technology and Design continues to exist at university level in Zimbabwe despite policies that have been put in place. Data were collected from 30 Textile Technology and Design lecturers and undergraduates pooled from two universities. The study embraced the interpretive paradigm, a qualitative approach and the case study design. It used open-ended questionnaires, face-to-face semi-structured interviews and focus group discussions to collect data. Data were analysed thematically. The study found out that gender disparity continued to exist in universities as a function of, among other things, gender stereotypes, gender irresponsive teaching and learning materials, lowering the cut-off entry points for females and lack of motivation for males. The major recommendations were the need for the Government’s intervention in funding male undergraduates in order to motivate them, lowering males’ cut-off entry points, conscientising communities on the importance of Textile and Technology Design and using gender responsive resources and environments that are free from gender discrimination.